2016
DOI: 10.2217/epi.15.110
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Response to Methadone: Genome-Wide DNA Methylation Analysis in Two Independent Cohorts

Abstract: Our results indicate that differentially methylated sites are associated with methadone daily dose and give insights into the molecular pathways underlying this interindividual dose variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…To the best of our knowledge, there is only one previous report of the potential modulation of LRP1B in human addiction. A decrease in the DNA methylation of the LRP1B promoter was found in blood cells from patients stabilized at high daily methadone doses compared with patients stabilized at low doses 52 . Interestingly, in that previously published sample 53 , a high methadone dose was significantly associated with lifetime cocaine dependence.…”
Section: Discussionmentioning
confidence: 86%
“…To the best of our knowledge, there is only one previous report of the potential modulation of LRP1B in human addiction. A decrease in the DNA methylation of the LRP1B promoter was found in blood cells from patients stabilized at high daily methadone doses compared with patients stabilized at low doses 52 . Interestingly, in that previously published sample 53 , a high methadone dose was significantly associated with lifetime cocaine dependence.…”
Section: Discussionmentioning
confidence: 86%
“…Work in humans generally relies on postmortem tissue from long-term drug users, and studies have found significant epigenetic differences in the brains of former addicts compared to non-addicts [21,22]. While the brain is the most relevant tissue in terms of neuroadaptation and drug-seeking behavior, epigenetic markers of addiction have also been detected in peripheral tissues such as the blood and sperm [23][24][25][26][27][28]. Easily accessible peripheral tissues are clearly the practical choice when it comes to defining biomarkers of drug use and/or predictors of individual risk for addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Work in humans generally relies on postmortem tissue from long-term drug users, and studies have found significant epigenetic differences in the brain of former addicts compared to non-addicts [21, 22]. While the brain is the most relevant tissue in terms of neuroadaptation and drug seeking behavior, epigenetic marks of addiction have also been detected in peripheral tissues such as blood and sperm [2328]. Easily accessible peripheral tissues are clearly the practical choice when it comes to defining biomarkers of drug use and/or predictors of individual risk for addiction.…”
Section: Introductionmentioning
confidence: 99%